On solutions of a quasilinear almost triangular system of difference equations - Shchegolev, S. A. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
For an almost triangular system of difference equations, the problem of existence of particular solutions in the form of Fourier series with slowly varying coefficients and frequency is studied.